Hyoroformylati on in homogeneous phase of eugenol ano isoeugenol with (RhCl(n4-1,5-COD)(2-ampy)) y (RhCl(PPh3)2(2-ampy)2)Complexes (Revista de Investigaciones Universidad del Quindío, 2011)
In this study, a synthesis with (RhCl(n4-1,5-COD)) and (RhCl(PPh3)2(2-ampy)2) ( COD= cyclooctadiene, 2-ampy= 2-aminopyridine and PPh3= triphenylphosphine) complexes was conducted. The compound (RhCl(PPh3)2(2- ampy)2, presents a doublet to 29.4 ppm, with o coupling constant of Rh-P of 86 Hz, indicating that the triphenylphosphine are in positíon trans. Compounds were active in the hydroformylation with eugenol and isoeugenol, in which the selectivity and catalytic activity depend on several factors such as the steric hindrance in the ligand, electronic factors and reaction temperature. The complex with phosphine ligands presented a minor catalytic activity, but a major selectivity towards linear aldehydes
Keywords: Hydroformylation; Rhadium; triphenylphosphine ligands; Eugenol; isoeugenol; 2-aminopyridine ligands